Mediale und soziale Bedingtheit der Subjekte des Privaten – ein Versuch mit Hannah Arendt - Matzner, Tobias (Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Proof-Carrying Hardware Versus the Stealthy Malicious LUT Hardware Trojan - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Applied Reconfigurable Computing)
Reconfigurable hardware has received considerable attention as a platform that enables dynamic hardware updates and thus is able to adapt new configurations at runtime. However, due to their dynamic nature, e.g., field-programmable gate arrays (FPGA) are subject to a constant possibility of attacks, since each new configuration might be compromised. Trojans for reconfigurable hardware that evade state-of-the-art detection techniques and even formal verification, are thus a large threat to these devices. One such stealthy hardware Trojan, that is inserted and activated in two stages by compromised electronic design automation (EDA) tools, has recently been presented and shown to evade all forms of classical pre-configuration detection techniques. This paper presents a successful pre-configuration countermeasure against this ``Malicious Look-up-table (LUT)''-hardware Trojan, by employing bitstream-level Proof-Carrying Hardware (PCH). We show that the method is able to alert innocent module creators to infected EDA tools, and to prohibit malicious ones to sell infected modules to unsuspecting customers.

VimaS_num: Measuring situational perception in mathematics of early childhood teachers - Bruns, Julia; Gasteiger, Hedwig (Proceedings of the 43rd Conference of the International Group for the Psychology of Mathematics Education)

Mathematikdidaktischen Wissen von frühpädagogischen Fachkräften aus kognitiv-situationsbezogener Perspektive – Theoretisches Konstrukt und empirische Erfassung - Bruns, Julia; Gasteiger, Hedwig (Beiträge zum Mathematikunterricht 2019)

Implementing a Real-time System on a Platform FPGA operated with ReconOS - Lienen, Christian

Federal Judge Ideology: A New Measure of Ex Ante Litigation Risk - HUANG, ALLEN; HUI, KAI WAI; Li, Reeyarn (Journal of Accounting Research)
ABSTRACT Drawing on the political theory of judicial decision making, our paper proposes a new and parsimonious ex ante litigation risk measure: federal judge ideology. We find that judge ideology complements existing measures of litigation risk based on industry membership and firm characteristics. Firms in liberal circuits (the third quartile in ideology) are 33.5% more likely to be sued in securities class action lawsuits than those in conservative circuits (the first quartile in ideology). This result is stronger after the U.S. Supreme Court's ruling in the Tellabs case. We next show that the effect of judge ideology on litigation risk is greater for firms with more sophisticated shareholders and with higher expected litigation costs. Furthermore, judicial appointments affect litigation risk and the value of firms in the circuit, highlighting the economic consequences of political appointments of judges. Finally, using our new measure, we document that litigation risk deters managers from providing long‐term earnings guidance, a result that existing measures of litigation risk cannot show.
Keywords: Economics and Econometrics; Finance; Accounting

Remaining useful lifetime prediction based on adaptive failure thresholds - Bender, Amelie; Schinke, Lennart; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
Remaining useful lifetime (RUL) predictions as part of a condition monitoring system are focused in more and more research and industrial applications. To establish an efficient and precise estimate of the RUL of a technical product, different uncertainties have to be handled. To minimize the uncertainties of the RUL estimation, a reliable and accurate prognostic approach as well as a good failure threshold are important. Regarding the failure threshold, most often an expert sets a fixed failure threshold. However, neither the a priori known failure threshold nor a fixedthreshold value are feasible in every application. Especially in the case of varying characteristics of the monitored system, an adaptive failure threshold is of great importance concerning the accuracy of the RUL estimation. Rubber-metal-elements, which are used in a wide range of applications for vibration and sound isolation, are mon-itored by thermocouples to allow for lifetime predictions. Therefore, the element’s state is described by its temper-ature during its service life. Aiming to establish accurate RUL predictions of a rubber-metal-element, uncertainties due to nonlinear material characteristics and changing operational conditions have to be considered. Consequently, different temperature-based failure threshold definitions are implemented and compared within a particle filtering approach.
Keywords: RUL prediction; adaptive threshold; prognostics; condition monitoring

FPGAs im Rechenzentrum - Platzner, Marco; Plessl, Christian (Informatik Spektrum)